INCOME ANALYSIS OF BROILER CHICKEN FARMING: A CASE STUDY IN SINDANGKASIH VILLAGE, SOUTH KONAWE REGENCY, INDONESIA - Hairil Adzulyatno Hadini; Muh Haidir Hakim; Andini Sulfitrana; Wa Ode Haimansrah (AgriMu, 2026)
This study aimed to analyze the income and financial feasibility of broiler chicken farming in Sindangkasih Village, West Ranomeeto Subdistrict, South Konawe Regency. The research was conducted from September to October 2024 using a purposive sampling method. Respondents consisted of two broiler farmers with production scales of 3,000 and 4,000 birds per cycle. Primary data were collected through interviews using questionnaires, while secondary data were obtained from relevant institutions. Data were analyzed using income analysis, R/C ratio, B/C ratio, and break-even point (BEP). The results showed that the average total production cost was IDR 116,195,931 per production period, consisting of fixed costs of IDR 2,345,931 and variable costs of IDR 113,850,000. Feed was the largest cost component, indicating its important role in determining profitability. The average total revenue was IDR 128,240,000, mainly derived from broiler sales and additional revenue from manure sales. The average income obtained was IDR 12,044,069 per production period. The R/C ratio was 1.10 and the B/C ratio was 0.10, indicating that the business was financially feasible. Furthermore, actual production and selling price were higher than the BEP quantity and BEP price. Therefore, broiler chicken farming in Sindangkasih Village is profitable and feasible to continue, although its sustainability depends on feed efficiency, mortality control, and price stability.